2020
DOI: 10.3389/fgene.2020.575678
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Statin-Induced Myotoxicity

Abstract: Statins, a class of lipid-lowering medications, have been a keystone treatment in cardiovascular health. However, adverse effects associated with statin use impact patient adherence, leading to statin discontinuation. Statin-induced myotoxicity (SIM) is one of the most common adverse effects, prevalent across all ages, genders, and ethnicities. Although certain demographic cohorts carry a higher risk, the impaired quality of life attributed to SIM is significant. The pathogenesis of SIM remains to be fully elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 261 publications
(402 reference statements)
1
20
0
4
Order By: Relevance
“…Here, we observed higher TC, non-HDL-C, and triglyceride levels in subjects carrying the C allele of this SNP. The CYP2C9 variants are worth investigating since this member of the cytochrome P450 family has a major role in the metabolism of most statins and has more than 60 reported genetic variants [ 35 ]. Moreover, we observed in both cohorts an association between higher HDL-C and the minor alleles of rs1532624 and rs708272 SNPs of CETP, a protein involved in the transfer of cholesteryl esters from HDL-C to other lipoproteins [ 36 ], confirming the results of several studies performed on a multitude of different ethnicities [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed higher TC, non-HDL-C, and triglyceride levels in subjects carrying the C allele of this SNP. The CYP2C9 variants are worth investigating since this member of the cytochrome P450 family has a major role in the metabolism of most statins and has more than 60 reported genetic variants [ 35 ]. Moreover, we observed in both cohorts an association between higher HDL-C and the minor alleles of rs1532624 and rs708272 SNPs of CETP, a protein involved in the transfer of cholesteryl esters from HDL-C to other lipoproteins [ 36 ], confirming the results of several studies performed on a multitude of different ethnicities [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seven SNPs from five different genes were identified through recent systematic reviews (Canestaro et al, 2014;Turner and Pirmohamed, 2019;Ward et al, 2019;Kee et al, 2020) and were selected based on their association with simvastatin and atorvastatin ADRs.…”
Section: Selection Of Statin Adr Variantsmentioning
confidence: 99%
“…Atorvastatin calcium (AC) is a widely used oral lipidlowering drug used in clinic for the treatment of hyperlipidemia [19,20]. However, adverse reactions have been reported related to myopathies and rhabdomyolysis [21]. It was reported that the plasma concentrations of AC and the risk of myopathies and rhabdomyolysis increase when combined with other medications [22,23].…”
Section: Grouping Of Hyperlipidemic Rats and Administrationmentioning
confidence: 99%